Towards an Inclusive Systemic Evaluation for the SDGs: Gender equality, Environments and Marginalized voices (GEMs). (April 2018) - Stephens, Anne; Lewis, Ellen D.; Reddy, Shravanti
With the advent of the United Nation's 2030 Sustainable Development Agenda, and its 17 Sustainable Development Goals, there is a call for more methodologies to understand and evaluate combinations of these global challenges, their integrated nature and their complexities. Accordingly, UN Women Independent Evaluation Office along with Australian and American researchers have written and piloted a new evaluation guide: Inclusive Systemic Evaluation for Gender equality, Environments and Marginalized voices (ISE4GEMs): A new approach for the SDG era (2018) . Referred to as the 'ISE4GEMs', this guide is an original piece of work that brings together transdisciplinary evaluation methods, re-thinks systemic evaluation methodology and introduces theG ender equality, E nvironments andM arginalized voices (GEMs) framework. This article provides a summary of the key theoretical concepts that have been synthesized from systems thinking, social and ecological sciences to produce process guidance.